Volume 8: Computational Fluid Dynamics (CFD) and Applications 2022
DOI: 10.1115/icone29-92595
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Simulation of Turbulent Heat Transfer of Liquid Metal Flow in a Narrow Rectangular Channel

Abstract: Liquid metal has the advantages of high boiling point and strong thermal conductivity and is selected as the coolant for a new generation nuclear system. In addition, the narrow rectangular channel is used in the small reactors or research reactors due to its compact structure and high heat transfer capacity. In order to accurately simulate the turbulent heat transfer of liquid metals in narrow rectangular channels, based on the relevant experimental data, this paper explored suitable numerical simulation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The geometric size and boundary conditions fully refer to the above experimental conditions. In previous studies (Zhang et al, 2022b), after comparison and analysis, it was found that the turbulence model that selected the standard k-epsilon model, combined with the enhanced wall treatment model, was more reasonable. After grid independence analysis, the grid division method is as follows: 300 nodes are evenly divided along the flow direction of the channel.…”
Section: Cfd Modelsmentioning
confidence: 97%
See 3 more Smart Citations
“…The geometric size and boundary conditions fully refer to the above experimental conditions. In previous studies (Zhang et al, 2022b), after comparison and analysis, it was found that the turbulence model that selected the standard k-epsilon model, combined with the enhanced wall treatment model, was more reasonable. After grid independence analysis, the grid division method is as follows: 300 nodes are evenly divided along the flow direction of the channel.…”
Section: Cfd Modelsmentioning
confidence: 97%
“…In previous work, a global turbulent Prandtl number model suitable for narrow rectangular channels was studied (Zhang et al, 2022b). The DNS calculation results of Kawamura et al (1999) showed that there is a certain relationship between the turbulent Prandtl number and position, so it is necessary to research local turbulent Prandtl number models.…”
Section: A New Local Turbulent Prandtl Number Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The focus of the analysis is on the impacts of the collocation of various models on the Nusselt number, the flow redistribution phenomena, as well as the difference in flow and heat transfer capacity in channels. Our research team recently conducted research on simulation methods for flow and heat transfer of liquid metal in narrow channels, optimized turbulence models, evaluated the applicability of existing Pr t models (Aoki, 1963;Reynolds, , 1974;Jischa and Rieke, 1979;Cheng and Tak, 2006;Keshmiri et al, 2008), and proposed a local Pr t model and a global Pr t model, respectively (Zhang et al, 2022b). The comparison results showed that the local Pr t model had better applicability to changes in the cross-section of the flow channel.…”
Section: Introductionmentioning
confidence: 99%